A Review on the Role of TRP Channels and Their Potential as Drug Targets_An Insight Into the TRP Channel Drug Discovery Methodologies - Fallah, Hamideh P; Ahuja, Ekta; Lin, Haoquan; Qi, Jinlong; He, Qian; Gao, Shan; An, Hailong; Zhang, Jian; Xie, Yongzhen; Liang, Dong (Frontiers in Pharmacology, 2022)
Transient receptor potential (TRP) proteins are a large group of ion channels that control many physiological functions in our body. These channels are considered potential therapeutic drug targets for various diseases such as neurological disorders, cancers, cardiovascular disease, and many more. Improving our knowledge of technologies for their study is essential. In the present study, we reviewed the role of TRP channel types in the control of normal physiological functions as well as disease conditions. Also, we discussed the current and novel technologies that can be used to study these channels successfully. As such, Flux assays for detecting ionic flux through ion channels are among the core and widely used tools for screening drug compounds. Technologies based on these assays are available in fully automated high throughput set-ups and help detect changes in radiolabeled or non-radiolabeled ionic flux. Aurora's Ion Channel Reader (ICR), which works based on label-free technology of flux assay, offers sensitive, accurate, and reproducible measurements to perform drug ranking matching with patch-clamp (gold standard) data. The non-radiolabeled trace-based flux assay coupled with the ICR detects changes in various ion types, including potassium, calcium, sodium, and chloride channels, by using appropriate tracer ions. This technology is now considered one of the very successful approaches for analyzing ion channel activity in modern drug discovery. It could be a successful approach for studying various ion channels and transporters, including the new members of the TRP family of ion channels.